Ingerencja państwa w wewnętrzne sprawy związków religijnych na podstawie sprawy Hosanna-Tabor Evangelical Lutheran Church and School v. EEOC - Kralka, Bartosz; Kossak, Dominik (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The purpose of this paper is to compare the state’s influence on the internal affairs of religious communities in the United States and Poland. The starting point of our article was the issue of Cheryl Periche in which the US Supreme Court addressed the fundamental principle of the independence of religious organizations, namely self-selection of their clergy. The study addresses aspects of the formation of religious freedom and the place of religion in the public life of the United States. Polish law pays close attention to the teaching of religion in public schools, freedom to act of apostasy in the Catholic Church, and we referred to judgments of the European courts on similar subjects. Based on extensive analysis of both legal systems we have found that both the Polish and American legislator protects the right of religious communities to self-determination.
Keywords: First Amendment; Religious autonomy; Pastor; EEOC; Perich; freedom of religion